The call of Cthulhu : for beginning readers - Ivankovic, R. J. (Chaosium, Inc., 2017)
"The late Professor Angell's research has been discovered by his grand-nephew, Francis Wayland Thurston. Francis delves into the papers and discovers a bas-relief depicting an odd creature with an octopoid head, spurring him to read on. He learns of the raid led by Inspector Legrasse and the voyage of the Vigilant, captained by Gustaf Johansen."--